2016
DOI: 10.12688/f1000research.6890.2
|View full text |Cite
|
Sign up to set email alerts
|

Fascial Manipulation® for chronic aspecific low back pain: a single blinded randomized controlled trial

Abstract: Background: The therapeutic approach to chronic aspecific low back pain (CALBP) has to consider the multifactorial aetiology of the disorder. International guidelines do not agree on unequivocal treatment indications. Recommendations for fascial therapy are few and of low level evidence but several studies indicate strong correlations between fascial thickness and low back pain. This study aims at comparing the effectiveness of Fascial Manipulation® associated with a physiotherapy program following guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Studies on the effectiveness of fascial mobilization are rare. Branchini et al [19] compared exercise and manual therapy with fascial mobilization therapy. They observed that there was a further decrease in pain, especially in the group treated by fascial mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effectiveness of fascial mobilization are rare. Branchini et al [19] compared exercise and manual therapy with fascial mobilization therapy. They observed that there was a further decrease in pain, especially in the group treated by fascial mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Fascia manipulation is conducted at strictly defined points in a specific area, so that the friction during manipulation would cause an increase in the temperature of the fascia tissue [9,10]. This leads to the destruction van der Waals and hydrophobic forces which hold together the hyalurnian chains [16]. The increase of the temperature in tissues causes decrease in hyalurnian viscosity [12,21] and an increase its ability to slide [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…After movement and palpatory verification, receiving the most active points of cc (coordination centre) of the common plane, and balancing it with the points of the antagonistic plane, takes place [8,9]. Fascia manipulation causes shift of friction into heat and creates inflammation in the manipulated site and this, in consequence, leads to modification of the consistency of the primary substance [8,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature in this area clearly reveals that few authors treat fascia as a three-dimensional system [76][77][78]. Nevertheless, it has been repeatedly pointed out that manual therapy based on the concept of tensegration (structural integration) is one of the most effective methods of balancing tensions within the motor organ in LBP therapy [79,80].…”
Section: The Merits Of the Issuementioning
confidence: 99%